Clinical efficiency of an education program for patients with rheumatoid arthritis - Evgenia Vladislavovna Orlova; L N Denisov; A O Arsenyev; N M Kosheleva; D E Karateyev; E L Nasonov (Научно-практическая ревматология)
Objective: to develop an education program for patients with rheumatoid arthritis (RA) and to evaluate its efficiency. Subjects and methods. The study included 43 patients with RA: 23 study group patients were trained according to an education program (Rheumatoid Arthritis Health School), 20 patients formed a control group. The education program consisted of 4 daily 90-min studies. The MDHAQ (R798—NP2) questionnaire was used to determine DAS 28, HAQ, RAPID 3 scores at baseline and following 6 months. Results. Six months after education, the study group showed reductions in DAS 28 by 1.33+0.26 scores (р < 0.05), HAQ by 0.91±0.54 (55.2%; р < 0.01), and RAPID 3 by 5.96±0.92 (49.9%; р < 0.01), anxiety level by 0.86±0.32 (54.4%; р < 0.05), depression by 0.87±0.61 (53.4%; р < 0.05), fatigability by 3.39±1.17 (47.5%; р < 0.05); sleep improved by 0.81±0.36 scores (54.7%; р < 0.05). Six months following education program participation, there was significantly more frequently a good DAS 28 response to treatment according to the EULAR criteria (52.2% versus 30.0% in the control group; р < 0.05), and the number of patients who reported health improvement increased by 8.5 times (р < 0.01). The changes in the control group were less pronounced, which determined statistically significant differences between the groups in most indicators (р < 0.05). Conclusion. The education program improves functional capacities and psychological status, assists in controlling the disease activity, and enhances the quality of life in patients with RA.